2014
DOI: 10.1111/adj.12164
|View full text |Cite
|
Sign up to set email alerts
|

Management of traumatically intruded young permanent tooth with 40‐month follow‐up

Abstract: Background: Intrusive luxation injuries often result in severe damage to the tooth, periodontal ligament and pulpal tissue. Furthermore, treatment outcome is often unpredictable because of the large number of injury related variables which influence choice of treatment and prognosis. This report presents the case of a 9-year-old boy with a 6 mm intruded permanent maxillary central incisor with an open apex. Methods: The treatment option chosen was to wait and watch for 'spontaneous re-eruption'. At the end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Studies suggested that intrusions up to 3.0 mm have an excellent prognosis, whereas intrusions greater than 6.0 mm have a poorer prognosis with higher chances of pulp necrosis and inflammatory root resorption (8)(9)(10). In the presented case, the depth of intrusion was 9.0 mm and the intruded tooth had a closed apex, with root length completed.…”
Section: Discussionmentioning
confidence: 78%
“…Studies suggested that intrusions up to 3.0 mm have an excellent prognosis, whereas intrusions greater than 6.0 mm have a poorer prognosis with higher chances of pulp necrosis and inflammatory root resorption (8)(9)(10). In the presented case, the depth of intrusion was 9.0 mm and the intruded tooth had a closed apex, with root length completed.…”
Section: Discussionmentioning
confidence: 78%
“…It has been shown that immature teeth present a better prognosis than do those with complete root formation. 3,6,9,14 Despite the implementation of an identical procedure in case report 2, eruption under traction proceeded unsatisfactorily and radiological examination revealed ankylosis. Therefore, a corticotomy and luxation were administered as supportive treatment to hasten re-eruption.…”
Section: Discussionmentioning
confidence: 93%
“…17 Of all the factors affecting prognosis, severity of intrusion is considered to be the most critical. 7,18,19 Intrusions up to 3 mm have been shown to have excellent prognosis, whereas intrusions > than 6mm have poor prognosis with greater chances of pulp necrosis and inflammatory root resorption.…”
Section: Case Reportmentioning
confidence: 99%